Stakeholder acceptance of a robot-assisted social training scenario for autistic children compared to a tablet-computer-based approach - Frenkel, Jonas; Kirst, Simone; Naumann, Sandra; Simon, Martina; Seßner, Julian; Roesler, Eileen; Onnasch, Linda; Dziobek, Isabel (Scientific Reports, 2025)
Recent studies indicate the potential benefits of robot-assisted therapy (RAT) for children on the autism spectrum (AS), yet acceptance among stakeholders remains unclear due to methodological shortcomings in existing research. This study evaluates stakeholders’ acceptance of a RAT-scenario designed to train emotion recognition and regulation in AS children using Softbank Robotics Pepper, a humanoid robot with an integrated tablet screen, compared to a tablet-based therapy (TBT) control. An online survey of 123 stakeholders (caregivers, professionals, and autistic adults) assessed RAT and TBT using global acceptance, intention to use, and acceptance-related factors (ALMERE model), alongside stakeholders’ concerns. While a larger proportion of stakeholders (58%) showed high global acceptance of RAT, stakeholders preferred TBT across measures and groups (p <.001, Wilk’s Λ = 0.595), potentially due to its established familiarity and easier usability. The intention to use RAT was predicted by perceived usefulness, and, to a smaller extent, perceived ease of use, and affinity for technology, independent of stakeholder group. Concerns mainly addressed the expected effort to implement RAT in therapeutic services. Overall, the results highlight stakeholder acceptance and underscore the need to enhance RAT’s perceived usefulness and ease of implementation, suggesting a user-centered design approach for future deployments.
CRIS-Team Scopus Importer:2025-04-11